Going Gonzo: Crunchyroll, Anime Streaming, and Unpaid Digital Labour - Ristola, Jacqueline (Kinephanos, 2024)
This essay examines how anime streaming platform Crunchyroll leveraged fan labour to become an industry leader in the anime distribution market. Before becoming a global leader in streaming anime, the site was known in the mid-2000s as an anime piracy site, largely functioning on fan labour for uploading its content. This essay combines Marxist political economy, discursive analysis, and fan studies methodologies to analyze how Crunchyroll capitalized on unpaid fan labour to transform itself from a popular piracy site into a legitimate streaming platform.